2017
DOI: 10.1186/s12889-017-4663-3
|View full text |Cite
|
Sign up to set email alerts
|

Local measles vaccination gaps in Germany and the role of vaccination providers

Abstract: BackgroundMeasles elimination in Europe is an urgent public health goal, yet despite the efforts of its member states, vaccination gaps and outbreaks occur. This study explores local vaccination heterogeneity in kindergartens and municipalities of a German county.MethodsData on children from mandatory school enrolment examinations in 2014/15 in Reutlingen county were used. Children with unknown vaccination status were either removed from the analysis (best case) or assumed to be unvaccinated (worst case). Vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In Germany, vaccines are given by private physicians or general practitioners in their offices. 25,26 Vaccines recommended by the German Standing Vaccination Committee (STIKO) are available free of charge through the statutory insurance policy. 24 In India, most vaccines recommended by the Indian Academy of Pediatrics (IAP) are provided free of charge.…”
Section: Country-specific Group Selectionmentioning
confidence: 99%
“…In Germany, vaccines are given by private physicians or general practitioners in their offices. 25,26 Vaccines recommended by the German Standing Vaccination Committee (STIKO) are available free of charge through the statutory insurance policy. 24 In India, most vaccines recommended by the Indian Academy of Pediatrics (IAP) are provided free of charge.…”
Section: Country-specific Group Selectionmentioning
confidence: 99%
“…At present, many parents forego vaccinations. Negative opinions that undermine the effectiveness and safety of preventive vaccinations as a form of infection prevention are widely disseminated [26].…”
Section: Discussionmentioning
confidence: 99%
“…On online portals and forums, there is information regarding the harmfulness of preventive vaccinations, complications arising from vaccinations, and the impact of mercury on the emergence of autism, autoimmune diseases, or weakening of the body's resistance. Anti-vaccine content is also spread among those who use homeopathic and natural medicine [26]. A negative example of the dissemination of false information regarding vaccinations was the investigation by Wakefield, who put forward the concept of a relationship between the MMR vaccination and autism [27].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the federal states reveals a mixed picture. For historical reasons, we find a higher degree of institutionalization under the public health service in East German federal states, and that results in higher rates of vaccination [22,23].…”
Section: The Case Of Germany: the Rise Of New Steering Instrumentsmentioning
confidence: 97%
“…This lack of formalization had a negative effect on vaccination uptake. Although reimbursement is now guaranteed, "severe and potentially dangerous vaccination gaps occur locally" [22] as studies have shown with regard to measles. A comparison between the federal states reveals a mixed picture.…”
Section: The Case Of Germany: the Rise Of New Steering Instrumentsmentioning
confidence: 99%